Educação ambiental: análise da percepção ambiental na comunidade escolar face aos recursos hídricos da localidade do Arapari, Senador José Porfírio, Pará - MOURA, Cleide Rodrigues (2021)
Senador José Porífirio, who belongs to the state of Pará, is the cradle of two Conservation Units of which the Arapari Community is part. In this context, we can see the importance of Environmental Education for the conservation of Igarapé Arapari, around the Conservation Unit “Sustainable Development Reserve - RDS / Xingu”. Based on the information, an intervention project was conducted through a participatory workshop that has as its general objective to reflect on the importance of Environmental Education in the school space, regarding the process of sensitization of social subjects regarding water resources in the Arapari community. The specific objectives are: to analyze the environmental perception of the school community in relation to the Arapari stream pollution, as well as to evaluate the results obtained from the methodology used, considering the importance of water resources conservation. In this sense, some actions were carried out within the school space, through a participatory workshop, involving the EMEF School Community Ignácio Cury Gabriel; Representative of Social Movements; Pará State Biodiversity Forestry Development Institute - IDEFLOR BIO; PA - Arapari Farmers Association and students of the Field Education Course - UFPA, around the importance of water resources for the ecological balance and sustainable use of traditional families. Analyzing the results, it is emphasized that the pedagogical practices related to Environmental Education at EMEF Ignácio Cury Gabriel, are not frequently worked on, and that the approach to water resources, especially from Igarapé that supplies the Arapari community is not being inserted in the curriculum. School.